TRANSGENE MANUFACTURING: FROM TOOLS TO APPLICATIONS - Wasim, Saeeda; Ahmad, Sharique (International Journal of Research -GRANTHAALAYAH, 2024)
Genetic modification generation is an important intersection of genetic engineering and biotechnology and involves the integration of foreign genes into the genome of organisms to produce specific proteins or repair genetic abnormalities. The machine has many applications in medicine, agriculture and biotechnology. The evolution of genetically modified production technologies from traditional methods to advanced genetic engineering tools demonstrates their evolution. This review discusses various methods incorporating modern and advanced technologies and explores their applications and future prospects. Early models of genetic modification generally involved organisms modified to produce human insulin, followed by the evolution of animals and plants. Traditional methods such as microinjection, retrovirus-mediated gene transfer and embryonic stem cell -mediated gene transfer are important for the production of transgenic animals. Similarly, Agrobacterium-mediated transformation and biolistic transformation methods are used to produce genetically modified plants. Although useful, these methods often result in synergistic and differential gene expression. Made with genetic modification. This technology allows modification of the target with minimal impact on the target, thus increasing the predictability and efficiency of genetic modification. Additionally, CRISPR/Cas9’s ability to alter multiple genes simultaneously and adaptability to various organisms expands its applications in medicine and agriculture. Synthetic biology continues to advance genetic engineering by designing and building new biological materials and systems, enabling innovations such as genetic engineering, metabolic processes, and minimal genomes. Viral vectors such as adeno-associated virus (AAV), lentivirus, and adenovirus have unique advantages and clinical challenges. Nonviral vectors, including lipid nanoparticles, electroporated, and polymeric vectors, provide alternative delivery methods with varying efficacy and specificity. Painkiller. It can improve crop growth, livestock and disease resistance in agriculture. Applications of biotechnology include biofuels, biopharmaceuticals, and bioremediation. Future directions aim to improve delivery, expand applications, explore synthetic genomics, advance personalized medicine, and develop regenerative agriculture. In summary, with the influence of advances in genetic engineering and technology, genetically modified production has become a complex field with many applications. Its future promises transformative solutions to global challenges in health, food security and environmental sustainability. To reach its full potential, continuous innovation and ethical thinking are essential.